2013
DOI: 10.1104/pp.112.210104
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Carbon and Nitrogen Supply on Relationships and Connectivity between Metabolism and Biomass in a Broad Panel of Arabidopsis Accessions    

Abstract: Natural genetic diversity provides a powerful tool to study the complex interrelationship between metabolism and growth. Profiling of metabolic traits combined with network-based and statistical analyses allow the comparison of conditions and identification of sets of traits that predict biomass. However, it often remains unclear why a particular set of metabolites is linked with biomass and to what extent the predictive model is applicable beyond a particular growth condition. A panel of 97 genetically divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 71 publications
5
93
0
1
Order By: Relevance
“…As the biomass reaction does not comprise NO 3 2 , only the increase in the organic nitrogen can be examined. Moreover, it has been experimentally shown that the reduced overall nitrogen availability can almost be compensated by an elevated NO 3 2 assimilation (Sulpice et al, 2013). In support of this claim, the gene expression of the low-affinity NO 3 2 transport system is shown to be induced under low NO 3 2 concentrations (Wang et al, 2000).…”
Section: Cell Performance With Respect To Different Cellular Scenariosmentioning
confidence: 80%
See 1 more Smart Citation
“…As the biomass reaction does not comprise NO 3 2 , only the increase in the organic nitrogen can be examined. Moreover, it has been experimentally shown that the reduced overall nitrogen availability can almost be compensated by an elevated NO 3 2 assimilation (Sulpice et al, 2013). In support of this claim, the gene expression of the low-affinity NO 3 2 transport system is shown to be induced under low NO 3 2 concentrations (Wang et al, 2000).…”
Section: Cell Performance With Respect To Different Cellular Scenariosmentioning
confidence: 80%
“…In accordance with the authors, we stress that this differs from earlier nitrogen deficiency experiments, where strong nitrogen limitations were obtained. In contrast, the carbon limitation is experimentally realized via short-day conditions (8-hlight/16-h-dark cycle; Gibon et al, 2004Gibon et al, , 2009Stitt et al, 2007;Sulpice et al, 2013), which affect the starch accumulation during the day and result in a restriction of carbon availability at night Sulpice et al, 2013).…”
Section: Cell Performance With Respect To Different Cellular Scenariosmentioning
confidence: 99%
“…Plant metabolism is subject to ageor plant-size-dependent effects (Geronimo and Beevers, 1964;Meyer et al, 2007) and is modified in response to environmental changes such as photoperiod (Graf et al, 2010;Sulpice et al, 2014;Yang et al, 2016). These factors modified the metabolic network, as shown by the differing correlation networks in the two experiments (Figure 1; see also Sulpice et al, 2013) and a weakening of correlations in the cross-experiment comparison. Furthermore, the activities of some enzymes, such as FK, GK, G6PDH, FBP, fumarase, and SPS, showed high plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, network structure is altered by relatively small changes in growth conditions (Figure 1; see also Sulpice et al, 2013), indicating that connectivity is partly due to the coordinated regulation of metabolism by metabolic, environmental, or developmental cues. To determine if genetic regulation also contributes to the connectivity in central metabolism, we searched for pleiotropic loci at which several metabolic QTL colocalize.…”
Section: Pleiotropic Regulation Of Primary Metabolismmentioning
confidence: 99%
See 1 more Smart Citation